Architects, sustainability and the climate emergency : a political ecology - Raisbeck, Peter (Emerald Publishing Limited, 2022)
The promises, dreams and hopes of architects for future cities are now inextricably linked to climate change. Architects, Sustainability and the Climate Emergency: A Political Ecology chronicles how architects have shaped their ideas of the city--and sustainability--as knowledge of the climate emergency has unfolded. Have architects responded to the climate crisis too slowly? Describing a political ecology of architecture, Peter Raisbeck draws on architectural history, theory and practice, and the climate imaginaries of architects themselves. This exploration indicates how architects have viewed the climate emergency and positions architecture alongside the politics of climate and development studies. Raisbeck questions to what degree the traditional agency of architects leads to a political authority isolated from nature, human-environment systems and the nonhuman ecological subjects rapidly approaching tipping points. The fluidity of the climate emergency itself and its unfolding relationship to architectural knowledge suggests that new approaches, agencies and subjectivities are urgently required. As architects struggle to respond to the climate emergency, this book is an important and timely contribution to sustainability, climate and development debates. Architects, Sustainability and the Climate Emergency: A Political Ecology is a necessary provocation of a critical topic.